Pengaruh Character Strength, Resilience Terhadap Flourishing pada Guru Sekolah Dasar di Kecamatan Lubuk Begalung Padang - Mariana, Rina; Situmorang, Nina Zulida; Hidayah, Nurul (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Psychological resources are considered in enhancing individual potential, yet few studies have focused on positive psychological variables, especially among elementary school teachers. Character strength and resilience has been highly affected by the appearance of flourishing. Character strength makes a person strong and able to face life and difficulties, and resilience is good in protecting against stress. These two factors have contributed to the flourishing. The aim of this research was to the effect of character strength and resilience on flourishing of elementary school teachers in Lubuk Begalung District, Padang. The number of samples taken in this study were 187 teachers obtained by means of saturated sampling. The research method uses a quantitative approach using three scales (i.e., character strengths, resilience, and flourishing). Using an ex post facto design, regression, F test and t test. Results indicated a there is the effect of character strength and resilience simultaneously on flourishing of elementary school teachers in Lubuk Begalung District, Padang with F=132,475 R2=0,590, and p=0,000, As hypothesized, character strength partially a effect on flourishing of elementary school teachers in Lubuk Begalung District, Padang with beta=0,485, t=10,500, and p=0,000. Additionally, the results also revealed that resilience partially a effect on flourishing of elementary school teachers in Lubuk Begalung District, Padang with beta=0,204, t=5,435, and p =0,000.